Congratulations! It's Asperger's syndrome - Birch, Jen, 1955- (Jessica Kingsley Publishers, 2003)
One of the increasing number of people diagnosed with Asperger Syndrome in adulthood, New Zealand-born Jen Birch relates her story with humour and honesty, taking us through the years of frustration and confusion that led to her diagnosis in 1998. Now that she can put her life experiences into context, she candidly describes her continual search for 'normality', including her experiences at work, her difficulties with relationships, her time spent in psychiatric hospital and her struggle for correct diagnosis in a country where the syndrome is relatively unknown. Talking positively about how h.